Digital Microfluidic Biochips - Chakrabarty, Krishnendu (CRC Press, 2012)
Microfluidics-based biochips combine electronics with biochemistry, providing access to new application areas in a wide variety of fields. Continued technological innovations are essential to assuring the future role of these chips in functional diversification in biotech, pharmaceuticals, and other industries.